Differences in Performance Characteristics Among Four High-Throughput Assays for the Detection of Antibodies Against SARS-CoV-2 Using a Common Set of Patient Samples. Issue 2 (9th October 2020) - Manthei, David M; Whalen, Jason F; Schroeder, Lee F; Sinay, Anthony M; Li, Shih-Hon; Valdez, Riccardo; Giacherio, Donald A; Gherasim, Carmen
Abstract: Objectives: Serologic testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has experienced a changing landscape of available assays coupled with uncertainty surrounding performance characteristics. Studies are needed to directly compare multiple commercially available assays. Methods: Residual serum samples were identified based on SARS-CoV-2 reverse transcription polymerase chain reaction (RT-PCR) testing, clinical test results, and collection dates. Serum samples were analyzed using assays from four different manufacturers: DiaSorin anti–SARS-CoV-2 S1/S2 IgG, EUROIMMUN anti–SARS-CoV-2 IgG ELISA, Roche Elecsys anti–SARS-CoV-2, and Siemens SARS-CoV-2 Total antibody assays. Results: Samples from SARS-CoV-2 RT-PCR–positive patients became increasingly positive as time from symptom onset increased. For patients with latest sample 14 or more days after symptom onset, sensitivities reached 93.1% to 96.6%, 98.3%, and 96.6% for EUROIMMUN, Roche, and Siemens assays, respectively, which were superior to the DiaSorin assay at 87.7%. The specificity of Roche and Siemens assays was 100% and superior to DiaSorin and EUROIMMUN assays, which ranged from 96.1% to 97.0% and 86.3% to 96.4%, respectively. Conclusions: Laboratories should be aware of the advantages and limitations of serology testing options for SARS-CoV-2. The specificity and sensitivity achieved by the Roche and Siemens assays would be acceptable for testing in lower-prevalence regions and have the potential of orthogonal testing advantages if used in combination.